PENGELOLAAN BARANG MILIK DAERAH DI KABUPATEN BENGKALIS - mawarti, sri; Sujianto; Harapan Tua, R.F.S (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
Regional Property must be managed properly and correctly so that transparent, efficient, accountable, economical Management of Regional Property is realized and guarantees certainty of value. The regional government of Bengkalis Regency often faces in the management of Regional Property (BMD) is the limited human resources. who are experts/trained have resulted in the management of Regional Property/BMD in Bengkalis Regency not running optimally. This study aims to look at the constraints and causes in managing a regional property in Bengkalis Regency, Riau Province with the research method used, namely field trips, conducting interviews and documentation and then used qualitative analysis techniques. The results of this study show that in Bengkalis Regency the management of regional property has been running smoothly but there are still obstacles in carrying out regional property management in Bengkalis Regency, Riau Province.